An Experimental Study on a Composite Bonding Structure for Steel Bridge Deck Pavements - Xiaoguang Zheng (Hindawi Limited, 2021)
As one of the major contributors to the early failures of steel bridge deck pavements, the bonding between steel and asphalt overlay has long been a troublesome issue. In this paper, a novel composite bonding structure was introduced consisting of epoxy resin micaceous iron oxide (EMIO) primer, solvent-free epoxy resin waterproof layer, and ethylene-vinyl acetate (EVA) hot melt pellets. A series of strength tests were performed to study its mechanical properties, including pull-off strength tests, dumbbell tensile tests, lap shear tests, direct tension tests, and 45°-inclined shear tests. The results suggested that the bonding structure exhibited fair bonding strength, tensile strength, and shear strength. Anisotropic behaviour was also observed at high temperatures. For epoxy resin waterproof layer, the loss of bonding strength, tensile strength, and shear strength at 60°C was 70%, 35%, and 39%, respectively. Subsequent pavement performance-oriented tests included five-point bending tests and accelerated wheel tracking tests. The impacts of bonding on fatigue resistance and rutting propagation were studied. It was found that the proposed bonding structure could provide a durable and well-bonded interface and was thus beneficial to prolong the fatigue lives of asphalt overlay. The choice of bonding materials was found irrelevant to the ultimate rutting depth of pavements. But the bonding combination of epoxy resin waterproof and EVA pellets could delay the early-stage rutting propagation.